Heart detection and diagnosis based on ECG and EPCG relationships - Preecha Yupapin; None Wardkein; Preecha Yupapin; None Phanphaisarn; None Koseeyaporn; None Roeksabutr; None Roeksabutr; None Wardkein; None Koseeyapon (My University, 2011)
A new design of a system for preliminary detection of defective hearts is proposed which is composed of two subsystems, in which one is based on the relationship between the electrocardiogram (ECG) and phonocardiogram (PCG) signals. The relationship between both signals is determined as an impulse response (h(n)) of a system, where the decision is made based on the linear predictive coding coefficients of a heart's impulse response. The other subsystem uses a phase space approach, in which the mean squared error between the distance vectors of the phase space of the normal heart and abnormal heart is judged by the likelihood ratio test (Λ) value, on which the decision is made. The advantage of the proposed system is that a heart's diagnosis system based on the ECG and EPCG signals can lead to high performance heart diagnostics.
Keywords: Phonocardiogram; Impulse response; Human heart; Phonocardiography and Auscultation Techniques